Practical Guidance for the Expanded Implementation and Provision of Bispecific Antibodies for Diffuse Large B-Cell Lymphoma (DLBCL) Across Canada. - MacDonald, David; Puckrin, Robert; Skrabek, Pamela; Lam, Selay; Jayakar, Jai; Fleury, Isabelle; Lemieux, Christopher; Boutin, Mélina; Costello, Jacqueline (Current Oncology, 2025)
Simple Summary: Bispecific antibodies (BsAbs) are a relatively new treatment option for relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL). There is an opportunity to provide these medications in the community, with greater convenience for patients, but establishing such programs requires safe and effective administration, monitoring and management. In this paper, an expert working group of nine hematologists from across Canada provides guidance on setting up and enhancing BsAb programs for lymphoma. (1) Background: Bispecific antibodies (BsAbs) for the treatment of relapsed/refractory diffuse large B-cell lymphoma (R/R DLBCL) can be delivered in ambulatory healthcare settings; however, the safe and effective management of potential side effects, such as cytokine release syndrome (CRS), requires protocolized monitoring and management. (2) Methods: An Expert Working Group (EWG) of nine hematologists from across Canada, with experience in leading BsAb program implementation, combined a review of published literature, a comparison of national/provincial/regional guidance documents and protocols, and their professional experiences to produce an informed framework for BsAb program implementation in various healthcare settings. (3) Results: The EWG supports and recommends the progression of BsAb provision from predominantly inpatient hospital settings to community/ambulatory care settings closer to the patient's home. A seven-step implementation process is outlined to support the safe and effective establishment of such programs, from establishing leadership, through customization of protocols, to education and execution. Strategies and considerations are offered to overcome potential barriers and empower healthcare professionals who are working to establish or improve BsAb programs across Canada. (4) Conclusions: For patients with R/R DLBCL, the safe and effective provision of BsAbs closer to home is both feasible and preferred. This guidance is intended to support the efficient and effective setup or enhancement of BsAb programs in lymphoma.